Illuminating microflora: shedding light on the potential of blue light to modulate the cutaneous microbiome - Serrage, Hannah J.; O’ Neill, Catherine A.; Uzunbajakava, Natallia E. (Frontiers in Cellular and Infection Microbiology, 2024)
Cutaneous diseases (such as atopic dermatitis, acne, psoriasis, alopecia and chronic wounds) rank as the fourth most prevalent human disease, affecting nearly one-third of the world's population. Skin diseases contribute to significant non-fatal disability globally, impacting individuals, partners, and society at large. Recent evidence suggests that specific microbes colonising our skin and its appendages are often overrepresented in disease. Therefore, manipulating interactions of the microbiome in a non-invasive and safe way presents an attractive approach for management of skin and hair follicle conditions. Due to its proven antimicrobial and anti-inflammatory effects, blue light (380 -495nm) has received considerable attention as a possible 'magic bullet' for management of skin dysbiosis. As humans, we have evolved under the influence of sun exposure, which comprise a significant portion of blue light.A growing body of evidence indicates that our resident skin microbiome possesses the ability to detect and respond to blue light through expression of chromophores. This can modulate physiological responses, ranging from cytotoxicity to proliferation. In this review we first present evidence of the diverse blue light-sensitive chromophores expressed by members of the skin microbiome. Subsequently, we discuss how blue light may impact the dialog between the host and its skin microbiome in prevalent skin and hair follicle conditions. Finally, we examine the constraints of this non-invasive treatment strategy and outline prospective avenues for further research. Collectively, these findings present a comprehensive body of evidence regarding the potential utility of blue light as a restorative tool for managing prevalent skin conditions. Furthermore, they underscore the critical unmet need for a whole systems approach to comprehend the ramifications of blue light on both host and microbial behaviour.